2020
DOI: 10.1097/jcn.0000000000000719
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and Insomnia Symptoms in Persons With Heart Failure

Abstract: Background/Objective: Insomnia and insomnia symptoms are highly prevalent in persons with heart failure (HF), and they are associated with several untoward outcomes. The purpose of this integrative review is to describe the correlates, predictors, and outcomes of insomnia and insomnia symptoms in persons with HF. Methods: Using integrative review methods, an extensive electronic search of 5 databases was conducted for the period of 2000-2019. Sixteen studies were identified that met the inclusion criteria for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
(233 reference statements)
0
11
0
Order By: Relevance
“…This analysis was part of a larger secondary data analysis of the health and retirement study (HRS) wave 2016 (Health and retirement study, 2019b). Details of the design and methods of the HRS study and the larger analysis were reported previously (Gharzeddine, 2020; Gharzeddine et al, 2021) and are summarized here for clarity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis was part of a larger secondary data analysis of the health and retirement study (HRS) wave 2016 (Health and retirement study, 2019b). Details of the design and methods of the HRS study and the larger analysis were reported previously (Gharzeddine, 2020; Gharzeddine et al, 2021) and are summarized here for clarity.…”
Section: Methodsmentioning
confidence: 99%
“…However, these associations were either not investigated or not reported as statistically significant in persons with HF. The lack of a large sample size could be attributed to the nonsignificant associations in these studies, and studies with large samples were deemed necessary (Gharzeddine et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, insomnia differs from poor sleep as a person may have poor sleep but not necessarily insomnia or insomnia symptoms (Sateia, 2014). Further, the associations between cognition and insomnia symptoms in persons with HF remains poorly understood since a limited number of studies have investigated these associations and reported mixed results (Gharzeddine et al, 2020). Given the significance of cognition and insomnia symptoms and their impact on clinical outcomes in persons with HF, there is a pressing need to examine these associations in this population.…”
mentioning
confidence: 99%
“…We hypothesized that cognitive impairment is associated with insomnia symptoms, and those with insomnia symptoms are more likely to have worse cognition compared to those without. This analysis was part of a larger study (Gharzeddine, 2020) that explored the associations of insomnia symptoms with sociodemographic, clinical, and lifestyle factors including associations with cognition and medication adherence, an essential component of self-care in persons with HF.…”
mentioning
confidence: 99%